Host alternation is necessary to maintain the genome stability of rift valley fever virus. - Sara Moutailler; Benjamin Roche; Jean-Michel Thiberge; Valérie Caro; François Rougeon; Anna-Bella Failloux (Public Library of Science (PLoS), 2011)
BACKGROUND: Most arthropod-borne viruses (arboviruses) are RNA viruses, which are maintained in nature by replication cycles that alternate between arthropod and vertebrate hosts. Arboviruses appear to experience lower rates of evolution than RNA viruses that replicate in a single host. This genetic stability is assumed to result from a fitness trade-off imposed by host alternation, which constrains arbovirus genome evolution. To test this hypothesis, we used Rift Valley fever virus (RVFV), an arbovirus that can be transmitted either directly (between vertebrates during the manipulation of infected tissues, and between mosquitoes by vertical transmission) or indirectly (from one vertebrate to another by mosquito-borne transmission). METHODOLOGY/PRINCIPAL FINDINGS: RVFV was serially passaged in BHK21 (hamster) or Aag2 (Aedes aegypti) cells, or in alternation between the two cell types. After 30 passages, these single host-passaged viruses lost their virulence and induced protective effects against a challenge with a virulent virus. Large deletions in the NSs gene that encodes the virulence factor were detectable from the 15(th) serial passage onwards in BHK21 cells and from the 10(th) passage in Aag2 cells. The phosphoprotein NSs is not essential to viral replication allowing clones carrying deletions in NSs to predominate as they replicate slightly more rapidly. No genetic changes were found in viruses that were passaged alternately between arthropod and vertebrate cells. Furthermore, alternating passaged viruses presenting complete NSs gene remained virulent after 30 passages. CONCLUSIONS/SIGNIFICANCE: Our results strongly support the view that alternating replication is necessary to maintain the virulence factor carried by the NSs phosphoprotein.